INOVASI PENGEMBANGAN MADRASAH BERBASIS TAHFIDZ; STUDI PENGEMBANGAN PROGRAM UNGGULAN DI MTS DAN MA TAQWIYATUL WATHON DEMAK - Ali Imron (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2020)
Islamic education institutions in the village of Sumberjo Mranggen, have developed the Tahfidz based curriculum. This policy was decided as a form of the curriculum innovation and development of the madrasah. This study aims to investigate more about the tahfidz-based education concept of madrasah of MTs and MA Taqwiyatul Wathon tahfidz al-Qur'an system and to seek out how the implementation of the curriculum development in the tahfidzbased madrasah education of MTs and MA Taqwiyatu Wathon, Sumberjo Mranggen, Demak, Central Java, Indonesia. The type and method of this research is descriptivequalitative research with a phenomenological approach of data collection techniques: in-depth interviews, observation, and documentation. The results show (1) the education concept emphasizes the time allocation for the tahfidz al-Qur'an with an extra portion, which additionally added hours to after-school period to attain tahfidz al- Qur'an 30 juz, but in fact this madrasah began to implement tahfidz-based concept from MI to MA purposing students to memorize and apply the contents of the Al-Qur'an in their daily life and (2) the tahfidzbased curriculum development of a madrasah education in MI, MTs and MA Taqwiyatu Wathon, Sumberjo Mranggen, Demak Regency, Central Java is applied to cover the needs for madrasah, development of educational goals, KTSP curriculum, Ministry of Religion curriculum and local content curriculum (Madrasah), learning experiences and curriculum evaluation.